Relaunching National Evaluation and Quality Assurance: Governing by Piloting - Joakim Lindgren; Linda Rönnberg; Agneta Hult; Christina Segerholm (Springer, 2022)
This chapter seeks to explore and discuss enactments in the process of piloting a part of the 2016 national evaluation and quality assurance system, namely, the pilot of institutional reviews in which higher education institutions’ internal quality assurance systems were evaluated by the Swedish Higher Education Authority. The chapter analyses the work and experiences of the different actors that took part in these processes. It shows that the pilot includes extensive work that links people, places, policies, practices, and power in particular ways and that numerous translations are made at different stages and by different actors. The results highlight the amount and forms of work done in these processes in general and in particular by actors who we have labelled “qualocrats”. Their embodied form of expertise is mobilised as they move between and across different domains to enact and promote certain knowledge in and of evaluation and quality assurance. The chapter finally suggests that the deliberate temporal design as a pilot study opened up for mutual adjustments, learning, and dialogue but also gave rise to contradictory anticipatory governing signals.
Evaluation-Knowledge Nexus : Swedish Higher Education as a Case